Non-noble metal fuel cell catalysts - Chen, Zhongwei; Dodelet, Jean-Pol; Zhang, Jiujun (Weinheim, Germany : Wiley-VCH, 2014)
Written and edited by top fuel cell catalyst scientists and engineers from both industry and academia, this is the first book to provide a complete overview of this hot topic. It covers the synthesis, characterization, activity validation and modeling of different non-noble metal electrocatalysts, as well as their integration into fuel cells and their performance validation, while also discussing those factors that will drive fuel cell commercialization. With its well-structured approach, this is a must-have for researchers working on the topic, and an equally valuable companion for newcomers to the field.
Description based on online resource; title from PDF title page (Wiley, viewed April 22, 2014)
Keywords: Fuel cells; Electrocatalysis; Electronic books